CHARACTERISTICS OF ADJUSMENT DISORDER IN BREAST CANCER PATIENTS (Vietnam Journal of Community Medicine, 2026)
Background: This study describes the characteristics of adjustment disorder in breast cancer patients. ICD-11 has re-conceptualized adjustment disorder into specific symptoms, making it more accessible for clinical diagnosis.Objectives: To describe the clinical characteristics of adjustment disorder among patients with breast cancer.Subjects and Methods: A cross-sectional descriptive study was conducted on 160 patients diagnosed with breast cancer, examined and treated at the Nuclear Medicine and Oncology Center – Bach Mai Hospital, during 2025-2026.Results: The prevalence of adjustment disorder was 26.3%. The primary stressors identified were the illness (54.8%), economic burden (31.0%), and metastasis (28.6%). Prominent core symptoms: preoccupation included excessive worry (85.7%) and recurrent thoughts (81.0%). Within the Failure to adapt to the stressor symptoms, sleep disturbance accounted for the highest proportion (90.5%). Key anxiety symptoms were nausea (40.5%), sweating (31.0%), and motor restlessness (28.6%). Notable depressive symptoms included thoughts of death (57.9%), reduced energy (47.6%), and hopelessness about the future (42.9%).Conclusion: Adjustment disorder was prevalent in 26.3% of breast cancer patients in this study. Stressors were mainly related to the disease pathology, financial burden, and the risk of metastasis.
Keywords: adjustment disorder, breast cancer.